Business families as stewards of sustainability - CHENG, John (Institutional Knowledge at Singapore Management University, 2021)
The drive to preserve the business for future generations makes family-owned enterprises especially suited to sustainability initiatives. Embracing ESG frameworks will help measure their effectiveness